STATUS PEKERJAAN, ETNIS, DAN PRESTASI AKADEMIK - Ijah ijah (Universitas Islam Syekh Yusuf, 2020)
The aims of this study was to determine whether there was influence of work status, ethnicity, lecture time and number of family members on academic achievement in the Teaching and Education Faculty of Syekh Yusuf Tangerang Islamic University both partially and simultaneously. This study uses a quantitative multiple regression method, with 124 samples taken using perposional random sampling of Teaching and Education Faculty students with a population of 180 students of FKIP UNIS Tangerang. Instrument for collecting data on employment status, ethnicity, lecture time, and number of family members (independent variables) using questionnaires in the form of students' personal data and academic achievement (dependent variables) using the student's personal data questionnaire. The results showed that job status, ethnicity, lecture time had no significant effect on academic achievement while the number of family members had a significant effect on academic achievement at FKIP UNIS Tangerang.Keywords: Job Status, Ethnicity, Lecture Time, and Academic Achievement.